Favna sesalcev (Mammalia) Brkinov - Karajič, Alije (Annales. Series historia naturalis, 1999)
The presence of 35 species of terrestrial mammals (Insectivora, Lagomorpha, Rodentia, Carnivora, Artiodactyla) are documented in the area of Brkini (south-western Slovenia). Four species are reported from this area for the first time: Neomys anomalus, Microtus agrestis, Martes martes and Mustela erminea, although populations of the last are marginal in Brkini. The study area is transitional between the continental and sub-Mediterranean parts of Slovenia, but its vegetation shows distinct sub-Mediterranean characteristics. Despite this, the Brkini mammal fauna (i.e. insectivores ...
Keywords: Brkini; Brkini Hills; favna; sesalci; zoologija; zoology